Farnesyltransferase inhibitor FTI-277 inhibits PD-L1 expression on septic spleen lymphocytes and promotes spleen lymphocyte activation. (14th July 2017) - Li, W; Tu, J; Liu, X; Yang, W
Summary: Farnesyltransferase inhibitors have been tested in clinical trials for the treatment of tumours. In sepsis, the binding of programmed death 1 (PD-1) to programmed death ligand 1 (PD-L1) promotes lymphocyte apoptosis and decreases cytokine expression, thus affecting survival rates. The PD-1/PD-L1 pathway plays an important role in chronic viral infection, bacterial infection and sepsis. However, the precise immunosuppressive and anti-inflammatory functions of this pathway remain poorly understood. In our previous study, the induction of sepsis by caecal ligation and puncture (CLP) resulted in increased farnesyltransferase activity and farnesylated protein levels in the spleen relative to sham treatment. However, the effect of inhibition of farnesyltransferase activity on overall survival rates in patients with sepsis and the specific signalling pathway involved remain to be investigated. In this study, mice with CLP-induced sepsis were treated with farnesyltransferase inhibitor (FTI-277), and PD-L1 expression on septic spleen lymphocytes was examined. Flow cytometric analysis revealed that PD-L1 is expressed constitutively on lymphocytes and that PD-L1 protein expression was up-regulated strongly following CLP. FTI-277 down-regulated PD-L1 mRNA and protein expression on septic spleen lymphocytes in a dose-dependent manner. This effect was associated closely with nuclear factor kappa B (NF-κB). In addition, the significant damping effect of FTI-277 on the PD-L1 signal promoted interferon (IFN)-γ secretion, interleukin (IL)-2 production and splenocyte proliferation in response to anti-CD3 + CD28 + antibodies in mice. Furthermore, FTI-277 reduced spleen lymphocyte apoptosis in septic mice. Therefore, FTI-277 regulates spleen lymphocyte activity via the PD-L1 signalling pathway, with significant anti-inflammatory effects attributable to suppression of the NF-κB pathway. Farnesyltransferase represents a valuable therapeutic target for the treatment of sepsis. Graphical Abstract: